Greening the Curriculum: A Strategic Waste Management for Chemical Wastes in School Laboratories - Jacqui Lou Baguios Valenzuela; Marilyn M. Blancaflor; Cynde Rose S. Solatorio; Edwin T. Anata; Juliet Salubre (JPAIR Institutional Research Journal)
Despite global awareness on the effects of improper chemical waste disposal, the actual practice of proper waste handling is still neglected. Serving as the best venue for information dissemination, schools can reinforce waste management programs through its curriculum. Identification of curriculum areas that can complement waste management strategies by evaluating the level of awareness and participation of its teaching employees, non-teaching staff, and students is the main objective of this study.  Validated self-constructed survey-questionnaires were administered to 149 respondents representing the total population of the laboratory teachers, students, non-teaching employees, and researchers of the Western Institute of Technology, Philippines whose primary job deals with chemicals. The data gathered and analyzed using student t-test showed that there is no significant difference in the level of awareness among teaching and non-teaching employees in terms of the school's chemical waste management program. A significant number of senior high school students showed lack of awareness on Philippine environmental laws and the chemical waste management in school.  Employees whose primary job is not associated with teaching and research do not realize their role in chemical waste minimization. More senior high school students show environmental concern over college students, but it is the latter group that apply the concepts of chemical waste management into actual practice.